Acceptance of illness and quality of life in patients with type 2 diabetes - Sylwia Anna Krzemińska; Anna Maria Kostka (Kazimierz Wielki University, 2021)
Background: results of studies concerning the quality of life in chronic diseases and the predictors thereof are a source of valuable information making it possible to take the right actions, both educational, at every stage, and therapeutic. The assessment acceptance of illness and the quality of life enables the identification of patients' actual problems and objections as well as the recognition of their needs for the purpose of treatment optimization. Objective: The aim of the study was to evaluate the acceptance of the disease and the quality of life of patients with type 2 diabetes. Materials and methods: The study assessed disease acceptance and the quality of life in 194 people living with type 2 diabetes for over 10 years. The AIS (Acceptance of Illness) and WHOQoL -BREF questionnaires were used. Results: Acceptance  of illness in the study group was average  24.21 points (SD=8.61). Patients are not satisfied with the quality of their life and their own health. According to the assessment of patients, the quality of their life is the highest in the social domain (mean13.72±2.18), slightly worse in the environmental domain (mean 13.31±2.1) and it is the worst in the mental (mean12.82±2.78) and physical (mean 12.02±3.24) domain. The AIS result significantly and positively correlated with each domain of life (all of them p<0.05), therefore, the higher the AIS result (better acceptance of illness). Conclusion: Acceptance of illness is an independent predictor of the quality of life in terms of the perception of own health and the perception of the quality of life in general. It also affects all domains of life.  The greater the acceptance of illness, the higher the quality of life in all domains.